Mid-regional pro-adrenomedulin as a marker of perioperative mortality in non-cardiac surgery - Golubović Mlađan; Stanojević Dragana; Jovanović Nenad; Lazarević Milan; Perić Velimir; Milić Dragan; Unić-Stojanović Dragana; Marković Dejan; Stošić Biljana; Stepanović Nemanja; Janković Radmilo (Vojnosanitetski Pregled)
nema